The Influence Of Sharia Marketing On The Decision Of Medical Beauty Clinic Guests In Choosing Services At Rumah Cantik Sehat Muslimah Yogyakarta - Qoirini Nur Azizah; Heri Prasetyo; Rr. Eko Giyartiningrum (UNIVED Press, 2024)
This study aims to determine the magnitude of influence on purchasing decisions (Y) on halal labels (X1), halal products (X2), and medical aesthetics (X3). Quantitative research methodology is the one applied. Data collection was carried out using questionnaires at Rumah Cantik Sehat Muslimah Gedongkuning Yogyakarta, with a sample of 92 respondents. With SPSS output, this study uses Data Quality Test, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. The study's findings suggest that medical aesthetics and halal labels influence consumer decisions. The variables of halal labels, halal products, and medical aesthetics influence purchasing decisions simultaneously, although halal products do not show a major influence on purchasing decisions.